2020
DOI: 10.1007/s11606-020-06067-8
|View full text |Cite
|
Sign up to set email alerts
|

Masks Do More Than Protect Others During COVID-19: Reducing the Inoculum of SARS-CoV-2 to Protect the Wearer

Abstract: Although the benefit of population-level public facial masking to protect others during the COVID-19 pandemic has received a great deal of attention, we discuss for one of the first times the hypothesis that universal masking reduces the "inoculum" or dose of the virus for the maskwearer, leading to more mild and asymptomatic infection manifestations. Masks, depending on type, filter out the majority of viral particles, but not all. We first discuss the near-century-old literature around the viral inoculum and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
216
0
13

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(235 citation statements)
references
References 36 publications
6
216
0
13
Order By: Relevance
“…While the role of a face mask in protecting other individuals is well-recognized, we observed that a face mask may also protect individuals who wear them, as has been described by others 29 . Alternatively, participants who generally are willing to wear a face (or self-report such) mask may also engage in overall healthier behaviors.…”
Section: Discussionsupporting
confidence: 77%
“…While the role of a face mask in protecting other individuals is well-recognized, we observed that a face mask may also protect individuals who wear them, as has been described by others 29 . Alternatively, participants who generally are willing to wear a face (or self-report such) mask may also engage in overall healthier behaviors.…”
Section: Discussionsupporting
confidence: 77%
“…However, this would be an emergency strategy and not a substitute for highly warranted vaccine strategies. In any case, preventive measures, such as social distancing, universal public masking, and application of standards of hygiene should be maintained to limit SARS-CoV-2 propagation [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Wenigstens aber hĂ€tte im letzten Satz des Artikels, wie ĂŒberall zuvor im Text, nur davon gespro-chen werden sollen, dass der MNB ein Baustein sein könnte, um Übertragungen zu reduzieren, nicht aber dies als Tatsache zu formulieren" [1] [37]. Gandhi et al [38] haben epidemiologische und klinische Befunde zusammengetragen, die dafĂŒr sprechen können, dass Masken (ĂŒber den Schutz anderer (Fremdschutz) hinaus) das "inoculum", d.h. die Dosis des Virus fĂŒr den MaskentrĂ€ger reduzieren (Eigenschutz) und zu milderen und asymptomatischen Verlaufsformen fĂŒhren könnten. Die Hypothese, dass das Tragen von Masken in der Öffentlichkeit helfen könnte, den Schweregrad der Erkrankung zu reduzieren und dazu beitragen könnte, dass ein grĂ¶ĂŸerer Anteil an neuen Infektionen asymptomatisch verlĂ€uft [38,39], bedarf dringend weiterer Untersuchungen.…”
Section: Diskrepanz Zwischen Analytischer Sorgfalt Und Unausgewogenenunclassified
“…Gandhi et al [38] haben epidemiologische und klinische Befunde zusammengetragen, die dafĂŒr sprechen können, dass Masken (ĂŒber den Schutz anderer (Fremdschutz) hinaus) das "inoculum", d.h. die Dosis des Virus fĂŒr den MaskentrĂ€ger reduzieren (Eigenschutz) und zu milderen und asymptomatischen Verlaufsformen fĂŒhren könnten. Die Hypothese, dass das Tragen von Masken in der Öffentlichkeit helfen könnte, den Schweregrad der Erkrankung zu reduzieren und dazu beitragen könnte, dass ein grĂ¶ĂŸerer Anteil an neuen Infektionen asymptomatisch verlĂ€uft [38,39], bedarf dringend weiterer Untersuchungen. Keine Frage, die "Variolation"-Hypothese ist eine Hypothese, aber eine, die deutlich besser begrĂŒndet ist als Ihre Sorge, Masken "mĂŒssen" 
 "im öffentlichen Raum sogar als ein Infektionsrisiko betrachtet werden" [1] (Seite 292) und ihre Schlussfolgerung, dass das Tragen von Masken im öffentlichen Raum "sogar potenziell kontra-produktiv" ... "ist" [1] (Seite 293).…”
Section: Diskrepanz Zwischen Analytischer Sorgfalt Und Unausgewogenenunclassified